2000
DOI: 10.1089/108729100318000
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD4:CD8 Ratio in Predicting HIV Co-infection in Patients with Newly Diagnosed Tuberculosis

Abstract: Because of the clinical implications of Human Immunodeficiency Virus (HIV) status on treatment of tuberculosis (TB) and in view of the low percentage of patients in whom HIV testing is performed, we evaluated immunological features of 54 patients with newly diagnosed TB and its ability to predict HIV co-infection. All 54 patients had initially unknown HIV status and had no other Acquired Immunodeficiency Syndrome (AIDS) defining illnesses. Twenty-two patients were found to be HIV seropositive and 32 were seron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…HIV-negative patients with TB are expected to have higher CD4 cell counts than those who are HIV-positive. In one study, when the immunologic features of 54 patients with newly diagnosed TB with unknown HIV status were evaluated, the median CD4 and CD8 counts were statistically different between the HIV-seropositive and HIV-seronegative patients, with the median CD4/CD8 ratio being 0.17 in HIVseropositive patients and 1.95 in the HIV-seronegative patients (P Ͻ 0.0001) (10). In a similar recently published study from Pune, India, significant differences in the CD4 counts and CD4/CD8 ratios between HIV-seropositive and HIV-seronegative TB patients were found.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-negative patients with TB are expected to have higher CD4 cell counts than those who are HIV-positive. In one study, when the immunologic features of 54 patients with newly diagnosed TB with unknown HIV status were evaluated, the median CD4 and CD8 counts were statistically different between the HIV-seropositive and HIV-seronegative patients, with the median CD4/CD8 ratio being 0.17 in HIVseropositive patients and 1.95 in the HIV-seronegative patients (P Ͻ 0.0001) (10). In a similar recently published study from Pune, India, significant differences in the CD4 counts and CD4/CD8 ratios between HIV-seropositive and HIV-seronegative TB patients were found.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been documented that there is significant role of CD4: CD8 ratio in predicting HIV co-infection in newly diagnosed TB. 8 It has been suggested that TB patients have a microenvironment that facilitates HIV infection by i) increasing the expression of co-receptors CXCR4 and CCR5 regulated by M. tuberculosis products; ii) increasing pro-inflammatory cytokines, especially TNF; and iii) down-regulation of CCL5. It has also been shown that M. tuberculosis and its cell wall component, lipoarabinomannan (LAM) may activate replication of HIV in provirus-carrying cells by inducing TNF and IL-6 production through the NF-kB pathway, which in turn triggers transcriptional activation of the long terminal repeat (LTR) promoter and supports replication of HIV.…”
Section: Introductionmentioning
confidence: 99%
“…In human, Salazar et al . [19] reported that the CD4:CD8 ratio was a useful parameter in predicting HIV-TB co-infection. In swine, a specific feature is that a substantial number of both CD4-CD8- and CD4+CD8+ T cells were found in peripheral blood [15,20-24].…”
Section: Introductionmentioning
confidence: 99%